Dietary Intervention Impacts Immune Cell Functions and Dynamics by Inducing Metabolic Rewiring - Okawa, Takuma; Nagai, Motoyoshi; Hase, Koji (Frontiers in Immunology, 2021)
Accumulating evidence has shown that nutrient metabolism is closely associated with various immune cell differentiation and functions. Cellular metabolism, including aerobic glycolysis, fatty acid oxidation, and oxidative phosphorylation, plays a key role in germinal center reaction, B-cell trafficking, and T-cell-fate decision. Furthermore, quiescent metabolic status consolidates T-cell-dependent immunological memory. Therefore, dietary interventions such as calorie restriction, time-restricted feeding, and fasting potentially manipulate immune cell functions. For instance, intermitted fasting prevents the development of experimental autoimmune encephalomyelitis. Meanwhile, the fasting response diminishes the lymphocyte pool in the gut-associated lymphoid tissue to minimize energy expenditure, leading to the attenuation of IgA response. The nutritional status also influences the dynamics of several immune cell subsets. Here, we describe the current understanding of the significance of immunometabolism in the differentiation and functionality of lymphocytes and macrophages. The underlying molecular mechanisms also are discussed. These experimental observations could offer new therapeutic strategies for immunological disorders like autoimmunity.